2022
DOI: 10.1021/acsenergylett.2c02408
|View full text |Cite
|
Sign up to set email alerts
|

How Stable Is the 2D/3D Interface of Metal Halide Perovskite under Light and Heat?

Abstract: A (PEA)2PbI4 (2D) layer deposited on a MAPbI3 (3D) film undergoes a transformation upon photoirradiation and thermal treatment. The decrease in absorption and emission of the 2D layer during light and heat exposure, which shows migration of the PEA+ cation within the 3D film, points out the dynamic nature of the 2D/3D interface and intermixing of the two phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 23 publications
3
39
0
Order By: Relevance
“…There is interest in raising the standard to 85°C ISOS-L-3 (MPP tracking at 85°C and 50% RH). However, the reactivity of ammonium ligands with 3D perovskites may lead to further penetration into the bulk perovskite film ( 28 , 31 , 32 ) and may contribute to deterioration in device performance under these very demanding stress conditions ( 27 , 28 , 31 33 ). Thus, we explored noninvasive surface-passivating ligands, but we did note that in prior studies, these have yet to achieve the remarkable benefits of the 2D/3D strategy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is interest in raising the standard to 85°C ISOS-L-3 (MPP tracking at 85°C and 50% RH). However, the reactivity of ammonium ligands with 3D perovskites may lead to further penetration into the bulk perovskite film ( 28 , 31 , 32 ) and may contribute to deterioration in device performance under these very demanding stress conditions ( 27 , 28 , 31 33 ). Thus, we explored noninvasive surface-passivating ligands, but we did note that in prior studies, these have yet to achieve the remarkable benefits of the 2D/3D strategy.…”
mentioning
confidence: 99%
“…There is a diversity of findings in reports on the stability of 2D overlayers under stress. Some studies have indicated limited stability of the 2D/3D interface under thermal stress (27)(28)(29). Progress has been made, with a recent study demonstrating 500-hour operating stability under conditions of 65°C, 50% relative humidity (RH), and maximum power point (MPP) tracking [International Summit on Organic Photovoltaic Stability (ISOS)-L-3-65°C], enhanced by the incorporation of 3-fluorophenethylammonium (3FPEA) intercalation (23).…”
mentioning
confidence: 99%
“…33 Interestingly, the S−S interaction within MTEA 2 PbI 4 provides no substantial advantage in terms of stability despite showing enhanced electronic properties, as recently proposed, 4 in line with previous reports. 34 Dispersion interactions, such as for PEA 2 PbI 4 , show a weak coupling of the organic framework, which may cause observed instabilities under elevated temperatures and permit percolation of bulky PEA cations into the 3D layer at the 2D/3D MHP interface 35,36 while the introduction of the halogen in aromatic cation such as I-PMA does not provide a substantial stabilization against PEA (see Table 1). We further emphasize that PEA 2 PbI 4 represents a lower limit of π−π interactions due to limited π-orbital overlap, which may be enhanced by tuning the aromatic cations.…”
mentioning
confidence: 99%
“…Note that an RP‐3D interface is reported to be kinetically unstable under thermal or light stresses, [ 36,37 ] with an activation energy as low as 0.38 eV. [ 38 ] Based on the above analysis, we believe the presented ACI phase can be considered as a final stable stage of an RP‐3D interface.…”
Section: Resultsmentioning
confidence: 93%